PENGARUH VARIASI LAMA KONTAK TANAMAN AZOLLA MICROPHYLLA TERHADAP PENURUNAN KADAR FOSFAT DAN COD PADA LIMBAH LAUNDRY - Nikita Rizky; Budiyono Budiyono; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Laundry is one kind of activities engaged in cloth laundering services. Laundry wastewater was discharged directly into the ditch and flowed to the river without treatment process. The level of COD and phosphate laundry wastewater was 761 mg/l, 20 mg/l exceeded the quality standard of Perda No. 5 of 2012. The research was aimed to know the effect of Azolla microphylla plants contact to the decrease of phosphate levels and COD. This kind of research used a quasi-experiment with the controlling group. The research object was the laundry liquid wastes from